EVALUASI PENGGUNAAN METODE VALUE ENGINEERING PADA PEKERJAAN KONSTRUKSI JEMBATAN SEI IDAN KABUPATEN KUTAI BARAT - Servasius Gervasius Zalukhu; Enik Rahayu (LPSDI Bina Patria, 2025)
This study aims to explore organizational culture and its impact on employee work motivation at Indomaret, Gembong branch, Karang Jati. The research employed a qualitative approach using in-depth interviews with nine informants, consisting of cashiers, store attendants, and logistics/warehouse staff. The findings reveal that organizational culture significantly influences employee motivation levels, although perceptions vary across divisions. Store attendants generally perceive the work culture as positive and exhibit high motivation. Cashiers show mixed perceptions, influenced by shift systems and daily workload conditions. In contrast, most logistics and warehouse staff experience high physical workloads, lack of appreciation, and low work motivation. These findings indicate that a participative, communicative, and fair work culture can effectively enhance employee enthusiasm and motivation. This study offers practical contributions for management in creating and fostering an organizational culture that supports employee well-being and productivity, particularly in the retail sector.